Pengembangan dan Uji Validitas Kuesioner Self Efficacy Pola Hidup Sehat Spiritual Islam - Murtiningsih, Murtiningsih; Sulistiyorini, Atik Oktora (Universitas Malahayati, 2024)
ABSTRACT Hospitalized patients may experience anxiety, which can impact the healing process. Complementary therapies, including Islamic spiritual therapy, can help reduce patient anxiety. Although there has been considerable research on Islamic spirituality, the ability of patients to independently manage their health by enhancing self-efficacy in healthy lifestyle patterns within Islamic spirituality has not been widely explored. Therefore, it is necessary to develop a questionnaire related to self-efficacy in healthy lifestyle patterns within Islamic spirituality. The objective of this study is to develop a questionnaire on self-efficacy in healthy lifestyle patterns within Islamic spirituality and to test its validity and reliability. The research method used is research and development (R&D) with a quantitative approach. The sample of this study consisted of 30 hospitalized patients selected through purposive sampling. The questionnaire includes 20 statements using a Likert scale. The results indicate that all items in the questionnaire are valid, with correlation coefficients exceeding the critical value of 0.361. The reliability test shows that the questionnaire is highly reliable, with a Cronbach's alpha of 0.954, indicating strong reliability as it is greater than 0.60. The conclusion of the study is that the questionnaire on self-efficacy in healthy lifestyle patterns within Islamic spirituality is valid and reliable. Future research should focus on educating patients on healthy lifestyle patterns within Islamic spirituality as a complementary therapy to enhance patient self-efficacy. Keywords: Validity, Reliability, Self-Efficacy, Healthy Lifestyle, Islamic Spirituality ABSTRAK Pasien yang dirawat di rumah sakit dapat menimbulkan kecemasan yang akan berdampak terhadap proses penyembuhan. Terapi komplementer sebagai pelengkap dari pengobatan secara farmakologi diantaranya yaitu terapi spiritual islam yang dapat mengurangi kecemasan pasien. Penelitan terkait spiritual Islam sudah banyak diteliti, akan tetapi bagaimana kemampuan pasien secara mandiri untuk merawat Kesehatan dengan meningkatkan self efikasi pola hidup sehat dalam spiritual Islam belum banyak dikembangkan. Sehingga perlu dikembangkan kuesioner terkait self efikasi pola hidup sehat dalam spiritual Islam. Tujuan penelitian ini adalah mengembangkan kuesioner self efikasi pola hidup sehat dalam spiritual Islam dan uji validitas dan reliabilitas kuesioner. Metode penelitian ini adalah research and development (R & D) dengan pendekatan kuantitatif. Sampel penelitian ini menggunakan purposive sampling sebanyak 30 pasien yang dirawat di Rumah Sakit. Kuesioner terdiri dari 20 pernyataan dengan menggunakan skala likert. Hasil penelitian menunjukkan semua kuesioner valid dengan nilai r hitung melebihi r table 0.361. Sedangkan uji reliabilitas menunjukkan kuesioner sangat reliabel dengan nilai alpha Cronbach 0.954 yang berarti reliabel karena >0.60. Kesimpulan penelitian bahwa kuesioner self efikasi pola hidup sehat dalam spiritual Islam adalah valid dan reliabel. Rekomendasi penelitian selanjutnya perlunya edukasi pola hidup sehat dalam spiritual Islam sebagai terapi komplementer untuk meningkatkan self efikasi pasien. Kata Kunci: Validitas, Reliabilitas, Self Efikasi, Pola Hidup Sehat, Spiritual Islam